2019
DOI: 10.3390/ijerph16050796
|View full text |Cite
|
Sign up to set email alerts
|

Real Foliage Plants as Visual Stimuli to Improve Concentration and Attention in Elementary Students

Abstract: This study was conducted to determine the physiological and psychological benefits of foliage plants as visual stimuli. Twenty-three elementary students (aged 11 to 13 years old) participated in this study. In a crossover design, electroencephalography (EEG) was used to measure and determine the psycho-physiological effects of four different visual stimuli: an actual plant, artificial plant, photograph of a plant, and no plant. Subjective evaluations of emotions were assessed using the profile of mood state an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…Many studies have reported the effect of viewing green plants on physiological relaxation. The findings confirmed that viewing green plants, such as foliage plants, in an indoor environment can elicit positive health outcomes with greater stabilization of prefrontal cortex activity and autonomic nervous activity [39,40,41,42,43,44,45,46,47,48].…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Many studies have reported the effect of viewing green plants on physiological relaxation. The findings confirmed that viewing green plants, such as foliage plants, in an indoor environment can elicit positive health outcomes with greater stabilization of prefrontal cortex activity and autonomic nervous activity [39,40,41,42,43,44,45,46,47,48].…”
Section: Resultssupporting
confidence: 62%
“…In particular, indoor experiments, where it is possible to control the stimuli and physical environment, entail more specific and diverse methodological approaches than those used in field experiments. Of the five senses, the effectiveness of sight [33,34,35,39,40,41,42,43,44,45,46,47,48,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74], smell [36,37,38,52,53,75] and touch [49,50,51] have been discussed. The rapid development of physiological indicators has enabled evaluation of body responses such as cerebral activity (functional magnetic resonance imaging [fMRI], near-infrared spectroscopy [NIRS] and electroencephalography [EEG]), autonomic nervous activity (heart rate variability [HRV], heart rate, pulse rate and blood pressure) and endocrine activity (salivary cortisol concentration).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each subject performed the study procedure as presented in Fig. 1 (Oh et al, 2019). Before starting the intensive assignment, subjects rested for 1 min by staring at a white wall.…”
Section: Methodsmentioning
confidence: 99%
“…Montessori (2013) reported that because nature directly educates humans, it is necessary to offer nature-based childhood education for a healthy body and mind. The results of EEG and subjective evaluations of emotions under green visual stimuli revealed improved concentration and psychological relaxation in elementary school students when they looked at real foliage plants compared with other visual stimuli (Oh et al, 2019). According to Markevych et al (2014), as the distance from residence to green space decreased, the occurrence of behavioral problems (e.g., emotional dysregulation, hyperactivity/inattention, and peer relationship problems) in children decreased.…”
mentioning
confidence: 97%